2012
DOI: 10.2118/146422-pa
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Gas Transport in Shales With Local Kerogen Heterogeneities

Abstract: On the basis of micro-and mesoscale investigations, a new mathematical formulation is introduced in detail to investigate multiscale gas-transport phenomena in organic-rich-shale core samples. The formulation includes dual-porosity continua, where shale permeability is associated with inorganic matrix with relatively large irregularly shaped pores and fractures, whereas molecular phenomena (diffusive transport and nonlinear sorption) are associated with the kerogen pores. Kerogen is considered a nanoporous org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
147
2
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(154 citation statements)
references
References 26 publications
1
147
2
4
Order By: Relevance
“…At this regime, the complex transport behavior is identified as transition flow. 20,21 When Knudsen number further increases (Kn > 10), it changes to free molecular flow due to the enhanced molecule-wall interaction. Clearly, the flow mechanisms of shale gas become more complicated with the decrease of pore size.…”
Section: Introductionmentioning
confidence: 99%
“…At this regime, the complex transport behavior is identified as transition flow. 20,21 When Knudsen number further increases (Kn > 10), it changes to free molecular flow due to the enhanced molecule-wall interaction. Clearly, the flow mechanisms of shale gas become more complicated with the decrease of pore size.…”
Section: Introductionmentioning
confidence: 99%
“…Дальнейшее увеличение числа Кнудсена 1 Kn > приводит уже к нарушению условия применимости механики сплош-ной среды, и течение становится свободномолекуляр-ным. В дополнение к описанному эффекту: в сланце-вых месторождениях с ультрамалыми размерами пор необходимо учитывать поверхностную диффузию [Akkutlu, Fathi, 2012], описывающую усредненное дви-жение под действием градиента концентрации адсор-бированных частиц, ставших подвижными в результа-те термической активации. Как показано в [Wu et al, 2015], в порах размера ~10 нм и меньше поверхностная диффузия превалирует над вязким и свободномолеку-лярным механизмами переноса газовой фазы.…”
Section: особенности моделирования гидрогеомеханических процессов воunclassified
“…have noticed the big differences between kerogen and inorganic matrix in shale and treat them separately [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Later, they [11] proposed a dual-porosity model to separate kerogen from inorganic matrix and pointed out that gas transport is dominated by Darcy flow in inorganic matrix while by non-Darcy flow in kerogen. They concluded that the permeability of shale is primarily relevant to the relatively large pore and fractures in inorganic matrix, but the molecular behaviors (diffusion transport and nonlinear adsorption) relevant to the pores in kerogen.…”
Section: Introductionmentioning
confidence: 99%